Need for Psychological Check-ups and Medical Treatment to the witnesses of Heinous Crimes - Archit Panwar; Komal Vig (Indian Journal of Forensic Medicine & Toxicology, 2021)
Witnesses are regarded as one of the most indispensable element in the criminal justice system. It is because of them that the trial finds some substance so as to arrive at a fair conclusion. The inputs provided by the witness may have direct bearing on the conviction or acquittal of an accused, hence it is desired that such witness be protected from the wrath of extraneous factors that have the capability to change his stance over a particular case. Extraneous factors in form of corruption or threats form a majority which results in turning of the witness hostile; hence it becomes rudimentary for the state to ensure protection of such witness so as not to alter the prescribed course of justice.